Awareness of the potential risks of printed pharmaceutical advertisements - Brent Knoesen; Ilse Truter; Louise Stroud (Acta Academica, 2009)
This article investigates consumer perceptions in the Nelson Mandela Metropole regarding printed advertisements of pharmaceutical products in order to identify potential risks. A focus group discussed various topics regarding pharmaceutical advertising. Thematic analysis was used as investigative tool. It was established that these advertisements evoke various desires, often contain irrelevant and false information that can lead to misinterpretation, and also often contain unintelligible jargon. Participants believed that photographs and pictures enhance the attractiveness and credibility of products. It was concluded that printed pharmaceutical advertisements present potential risks if misunderstood and/or misinterpreted.